No plastics detected in seal (Phocidae) stomachs harvested in the eastern Canadian Arctic. (January 2020) - Bourdages, Madelaine P.T.; Provencher, Jennifer F.; Sudlovenick, Enooyaq; Ferguson, Steven H.; Young, Brent G.; Pelletier, Nicolas; Murphy, Michael J.J.; D'Addario, Alexa; Vermaire, Jesse C.
Abstract: Through collaboration with Inuit hunters, we examined the stomach contents of 142 seals (ringed seals [ Phoca hispida ; n = 135], bearded seals [ Erignathus barbatus ; n = 6], and one harbour seal [ Phoca vitualina ; n = 1]) hunted between 2007 and 2019 from communities around Nunavut to assess whether seals in the eastern Canadian Arctic ingest and retain plastics in their stomachs. The seals in this study ranged from juveniles to adults of up to 30 years of age, and 55% of the seals were males. We found no evidence of plastic ingestion in any of the seals suggesting that seals in Nunavut are not accumulating plastics (>425 μm) in their stomachs. These data provide important baseline information for future plastic pollution monitoring programs in the Arctic. Highlights: Stomach contents of 142 seals from Nunavut examined for plastics >425 μm No evidence of plastic pollution was found in any of the seal stomachs. These data provide baseline information for future Arctic monitoring programs.